EL USO DE LA INTELIGENCIA ARTIFICIAL EN EL MARKETING INSTITUCIONAL DE LOS GOBIERNOS AUTÓNOMOS DESCENTRALIZADOS CANTONALES EN LOS RÍOS. - ROMERO OLEA JORGE JUNIOR (2024)
This research focuses on determining the use of artificial intelligence in the institutional marketing of the Cantonal Decentralized Autonomous Governments in the province of Los Ríos. In a context where digital transformation has become imperative to improve communication and interaction with citizens, we examine how AI can optimize the institutional marketing strategies of these government entities. The study is based on a review of the literature related to AI in the field of marketing, as well as the analysis of success stories both nationally and internationally. The main benefits that AI can bring to the institutional marketing of cantonal GADs are identified, such as the personalization of messages, optimization of resources, improvement in decision making and the creation of more satisfactory experiences for citizens. Additionally, the challenges and limitations that may arise when implementing AI in this context are examined, including ethical, privacy, and staff training issues. A conceptual framework is proposed for the integration of AI in institutional marketing strategies, which includes the identification of clear objectives, the appropriate selection of tools and technologies, and the continuous evaluation of results. Finally, a series of recommendations are presented for the cantonal GADs of Los Ríos that wish to adopt AI in their institutional marketing, which highlight the importance of interdepartmental collaboration, the formation of a multidisciplinary team and attention to the needs and expectations of the users. citizens.